Modelagem matemática na educação matemática brasileira : histórias em movimento - Magnus, Maria Carolina Machado (2018)
The present research was developed in 2 movements. In movement 1, I describe the history of Modeling, a story written from what counts the theses and dissertations defended in Brazil, from 1987 to 2016. The document history seeks an origin and shows the development of Modeling in a linear and evolutionary way, free of mishaps and discontinuities. In movement 2, the goal is to write the history of the present modeling - history monument - to show the conditions of possibilities for its emergence, the cracks that this discourse underwent in the course and the marks of the past in the present - its regularities. The theoretical-methodological contributions, which support the writing of monument history, are linked to the theorizations of the philosopher Michel Foucault. The analytical material covers theses and dissertations, annals of the National Conference on Modeling in Mathematics Education and interviews. The analysis of these materials evidenced that the emergence of the modeling discourse occurs in the midst of a crisis in the teaching of Mathematics, consisting of the following statements: “students have difficulty in learning Mathematics” and “Mathematics is distant from reality”. The scrutiny of the material also gives visibility to some discursive discontinuities: the modeling discourse when intertwining with the constructivist discourse, in the 1980s, displaces the sense of studying from models - product - to construct models – process; from the economic and political conditions experienced in Brazil, the discussion about the formation of a critical and reflective subject emerges in the 1990s, in the discursive plots of Modeling, evidencing that the discourse of Modeling is also an identity question. Afterwards, the analysis gives visibility to the modeling discourse as a mechanism for the privileging of the school content, showing that Modeling legitimizes and supports the curricular machinery and, also, is sustained and legitimized by it.